PENGARUH KOMBINASI PAKAN BUATAN DENGAN TEPUNG DAUN MANGROVE API – API (Avicennia marina) TERHADAP PERTUMBUHAN IKAN NILA SRIKANDI (Oreochromis aureus x niloticus). - Muh. Haritsah Arghifari; Rahmad Jumadi; Muh. Sulaiman Dadiono (Jurnal Perikanan Pantura (JPP), 2019)
Avicennia marina have been known for a long time by the community because of the many benefits they have and are commonly used as medicines, fuelwood or construction of house buildings, and also animal feed. Production of tilapia srikandi is currently being developed to increase fisheries production cultivation, tilapia srikandi (Oreochromis aureus x niloticus) has many advantages including fast to growth, disease resistance and tolerance to the environment. The purpose of this study was to determine the effect of artificial feed with the the addition of formulation from different Avicennia marina leaves to the growth of srikandi tilapia (Oreochromis aureus x niloticus). This study was conducted using a completely randomized design (CRD), with 3 treatments 3 replications and using 10 fish in each replication treatment. Treatment of A: 100% artificial feed, Treatment B: 25% artificial feed + 75% flour of Avicennia marina leaves, Treatment C: 50% artificial feed + 50% flour of Avicennia marina leaves, Treatment D: 75% artificial feed + 25% flour of Avicennia marina leaves. The results of this study indicate that the treatment of the effect of the combination of artificial feed with flour of Avicennia marina leaves on the growth of srikandi tilapia (Oreochromis aureus x niloticus). The variable of daily growth rate and survival variable get the best results in treatment C (50% artificial feed + 50% flour of Avicennia marina leaves), in the long variable absolute get the best results on treatment D (75% artificial feed + 25% flour of Avicennia marina leaves ), variable of absolute weight and FCR variable get the best results in treatment A (100% artificial feed).